Randai Art As Local Wisdom In Creating Local Tourism Innovation In Kuantan Singingi Regency - Made Devi Wedayanti (Iapa Proceedings Conference, 2018)
Seni Randai Kuantan, is a heritage art from traditional culture that used to grow and develop in Kuantan Singingi Regency. Randai in the Kuansing area called Randai Kuantan. Kuansing Regency has cultural tourism, one of which is Randai Performing Arts attractions. Randai Performing Arts is used as a tourist attraction because Randai is a unique folk art that is unique in delivering messages and entertainment. Therefore, Randai performance art can also be used as an added value innovation for local tourism managers so that it can increase the number of tourist visits. However, Randai is still rarely implemented and young women from Kuantan singing district have started to know that Randai art can become one of the mainstay alternatives to attract tourists to visit Kuantan Singingi Regency. This research is a type of qualitative research. The source of this research data is primary data obtained from interviews with informants and key informants. Data analysis is done by data reduction, data presentation and conclusion drawing. The conclusion of this study is based on respondents' responses to randai art attractions, respondents gave responses that the Randai show was interesting, the readiness of the community to make randai art a tourist attraction, the community responded that it was ready to make randai displayed as a tourist attraction and became a characteristic in Kuantan Tengah Subdistrict Kuantan Singingi Regency .